2000
DOI: 10.1161/01.atv.20.5.1236
|View full text |Cite
|
Sign up to set email alerts
|

Localization of CD9, an Enhancer Protein for Proheparin-Binding Epidermal Growth Factor–Like Growth Factor, in Human Atherosclerotic Plaques

Abstract: Abstract-Heparin-binding epidermal growth factor (EGF)-like growth factor (HB-EGF), a member of the EGF family, has a potent mitogenic activity for vascular smooth muscle cells (SMCs). We previously reported that HB-EGF is involved in atherogenesis of human aorta and coronary arteries. ProHB-EGF (the membrane-anchored form of HB-EGF) has also been demonstrated to possess a mitogenic activity, which is Ϸ30-fold increased when coexpressed with CD9 in mouse L cells. Thus, in the process of atherogenesis, CD9 may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…However, using the same assessment, sunitinib did not affect HASMC proliferation induced by HB-EGF, another mitogenic growth factor. 27,28 Moreover, the Boyden chamber assay showed that sunitinib also suppressed HASMC migration induced by PDGFs but not by HB-EGF. These results suggest that sunitinib may significantly and specifically inhibit PDGF-induced VSMC proliferation and migration.…”
Section: Sunitinib Suppresses Erk Phosphorylation and Receptor Autophmentioning
confidence: 99%
“…However, using the same assessment, sunitinib did not affect HASMC proliferation induced by HB-EGF, another mitogenic growth factor. 27,28 Moreover, the Boyden chamber assay showed that sunitinib also suppressed HASMC migration induced by PDGFs but not by HB-EGF. These results suggest that sunitinib may significantly and specifically inhibit PDGF-induced VSMC proliferation and migration.…”
Section: Sunitinib Suppresses Erk Phosphorylation and Receptor Autophmentioning
confidence: 99%
“…ProHB-EGF may serve a variety of functions depending on its cellular context and has been reported to be mitogenic and cytoprotective in some cells while growth inhibitory and proapoptotic in others (Iwamoto et al, 1999;Nishida et al, 2000;Takemura et al, 1997). ProHB-EGF has also been suggested to promote cell-cell adhesion (Kimber, 2000;Takemura et al, 1997).…”
mentioning
confidence: 99%
“…The functional significance of this elevated expression, however, has not yet been demonstrated. Elevated expression of CD9, an enhancer of pro‐HB‐EGF bioactivity, has also been reported in human atherosclerotic plaques 82. Based on the available data in cultured SMCs showing a requirement of EGFR activation by thrombin and angiotensin II, both regulators of SMC function in vivo , we hypothesize that the EGFR may have an important role in the arterial injury response.…”
Section: Is Epidermal Growth Factor Receptor Activation/transactivatimentioning
confidence: 71%
“…Elevated expression of CD9, an enhancer of pro-HB-EGF bioactivity, has also been reported in human atherosclerotic plaques. 82 Based on the available data in cultured SMCs showing a requirement of EGFR activation by thrombin and angiotensin II, both regulators of SMC function in vivo, we hypothesize that the EGFR may have an important role in the arterial injury response. It will be an important task to test this hypothesis and to delineate the function of the EGFR in vascular biology.…”
Section: Is Epidermal Growth Factor Receptor Activation/transactivatimentioning
confidence: 92%